2013
DOI: 10.3928/15394492-20131209-01
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Young Adults with High-Functioning Autism in Taiwan: A Pilot Study

Abstract: This pilot study aimed to investigate the activity participation of young adults with high-functioning autism (HFA) living in Taiwan. Eleven young adults with HFA, their caring adults, and 11 matched typically developing youth were recruited across Taiwan. The Adolescent and Young Adult Participation Sort-Taiwanese version (AYAPS-T) was administered to all three groups to compare the activity participation. In addition, youth with HFA identified activities in which they desired to participate and barriers hind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…We hypothesized that areas of difference would include lower levels of physical activity participation (Must et al 2014), skill and job/chore participation and similar participation in recreational activities , specifically sedentary use of electronics. Additionally, we expected the gap to become larger for the older children based on previously published research of decreased participation as youth approach young adulthood (Hilton et al 2008; McCollum et al 2016; Wang and Berg 2014). Understanding the participation patterns of children with ASD and where there are major gaps on the developmental trajectory has clinical implications for treatment of children with ASD and long term QOL.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We hypothesized that areas of difference would include lower levels of physical activity participation (Must et al 2014), skill and job/chore participation and similar participation in recreational activities , specifically sedentary use of electronics. Additionally, we expected the gap to become larger for the older children based on previously published research of decreased participation as youth approach young adulthood (Hilton et al 2008; McCollum et al 2016; Wang and Berg 2014). Understanding the participation patterns of children with ASD and where there are major gaps on the developmental trajectory has clinical implications for treatment of children with ASD and long term QOL.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, there is likely to be varying access to services between countries (Lin et al, 2012; Sun et al, 2013), which may mean differing amount of intervention to develop the skills and competence necessary for satisfying social participation. We found only one study examining participation patterns among young adults with ASD in Eastern countries (Wang and Berg, 2014). Consistent with cultural expectations, Wang and Berg (2014) found that youth with HFA in Taiwan engaged most frequently in sedentary leisure activities at home and had minimal social interactions.…”
Section: Introductionmentioning
confidence: 99%
“…This article describes the development of a new card sort, the Adolescent and Young Adult Activity Card Sort (AYA-ACS), for emerging adults who are encountering transitional challenges. An earlier version of this tool is referred to as the Adolescent and Young Adult Participation Sort (AYAPS) and AYAPS-T (Taiwan; Wang & Berg, 2013, 2014).…”
Section: Discussionmentioning
confidence: 99%